PENGARUH PENGETAHUAN INVESTASI, KEBIJAKAN MODAL MINIMUM DAN SOCIAL MEDIA INFLUENCER TERHADAP MINAT MAHASISWA BERINVESTASI - Amram Rohi Bire; Enos Kabu; Putri Patricia Tety (Politeknik Negeri Ambon, 2026)
Introduction: This study aims to examine the effect of Investment Knowledge, Minimum Capital Policy, and Social Media Influencers on Students’ Investment Interest.Method: This research employs a quantitative method with data analysis using Multiple Linear Regression, supported by SPSS software. The sample consists of 100 students who invest in stocks at the Indonesia Stock Exchange Investment Gallery across universities in East Nusa Tenggara.Results: The findings indicate that partially, Investment Knowledge, Minimum Capital Policy, and Social Media Influencers each have a significant effect on Students’ Investment Interest. Simultaneously, these three variables influence Students’ Investment Interest by 76%, while the remaining 24% is explained by other factors not examined in this study.Conclusion: The results confirm that Investment Knowledge, Minimum Capital Policy, and Social Media Influencers, both partially and simultaneously, have a significant impact on Students’ Investment Interest. These findings suggest that increasing students’ investment interest is not determined by a single factor but rather by the synergy between cognitive aspects (knowledge), structural policies (ease of initial capital), and socio-digital factors (influencer impact). The novelty of this study lies in the integration of these three variables into a comprehensive analytical model, particularly by positioning Social Media Influencers as a relevant variable in the context of current digital developments. This study offers a new perspective that strategies to enhance students’ investment interest should combine educational approaches, inclusive policies, and the effective use of social media as a communication tool. Keywords: Investment, Literacy, Risk, Shares